Metacognitive strategies of ESL learners with different listening abilities: a case study - Abdul Malik, Faridah (IIUM Press, International Islamic University Malaysia, 2011)
Metacognitive Strategies have been shown to contribute significandy to language learning success. Previous studies have also shown the important role that these Strategies play in ensuring success in listening comprehension. These studies have informed us that it was the differences in metacognitive Strategy use that differentiate skilled and less-skilled. Nevertheless, there is still a great deal to be discovered about these differences, not just quantitatively but also qualitatively. A close examination of the metacognitive Strategies used by learners with different listening abilities is needed. This paper presents findings from a case study examining the different ways in which skilled and less-skilled listeners different in their use of metacognitive listening Strategies. To find evidence of these metacognitive Strategy use, four sets of think-aloud protocols were analysed. The findings showed that the skilled and less-skilled listeners may possess the same types of metacognitive listening Strategies and the less-skilled listeners may use these Strategies more frequently, but, the skilled listeners were more successful at comprehension as their more developed metacognitive Strategy use enabled them to better regulate their top-down and bottom-up listening processes.